Showcasing the essence of motherhood and women in families: Insights from the Old Testament - Fritz William Malvern Steenkamp; Prof Fazel Ebrihiam Freeks (Pharos Journal of Theology, 2025)
This paper highlights that the notion of motherhood encompasses a wide range of perspectives within families. The significant role of mothers in contemporary Hebrew legal and moral systems is fundamental to this discussion. Motherhood extends beyond biological ties, involving responsibilities such as providing education, nutrition, a hygienic environment, and quality time with both parents. The reverence for motherhood is evident in biblical passages such as Exodus 20:12, Leviticus 19:3, 5:16, Deuteronomy 21:18, and 21:21. In Jewish tradition, the mother of the king holds a position of high esteem, as reflected in texts such as 1 Kings 2:29, Proverbs 10:1, 15:20, 17:25, 29:15, 31:1, and 31:31. For instance, King Solomon demonstrated profound respect for his mother, Bathsheba, by standing to honour her when she entered the throne room and seating her at his right hand to engage in important discussions.